Light-driven assembly of biocompatible fluorescent chitosan hydrogels with self-healing ability. Issue 42 (8th October 2020) - Guaresti, Olatz; Crocker, Leander; Palomares, Teodoro; Alonso-Varona, Ana; Eceiza, Arantxa; Fruk, Ljiljana; Gabilondo, Nagore
Abstract : Nitrile imine-mediated tetrazole-ene cycloaddition (NITEC) was successfully used to cross-link complementary tetrazole and maleimide chitosan derivatives into hydrogel networks using irradiation. Abstract : Nitrile imine-mediated tetrazole-ene cycloaddition (NITEC) was successfully used to cross-link complementary tetrazole and maleimide chitosan derivatives into hydrogel networks using irradiation. The photo-click reaction resulted in the formation of robust fluorescent hydrogels with an emission signal at around 530 nm. The degree of cross-linking and the resulting hydrogel properties such as pH sensitivity and swelling were influenced by the tetrazole/maleimide ratio and the length of irradiation. Interestingly, rheological studies demonstrated self-healing character of the novel hydrogels as indicated by instantaneous recovery of the storage modulus to the initial values under different oscillatory strains without any additional external trigger. Finally, in addition to their photo-tuneable and self-healing properties, the novel chitosan hydrogels were also found to be biocompatible and susceptible to in vitro enzymatic degradation, making them suitable for design of traceable biomaterials for biomedical applications.